(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The purpose of this study is to establishing the influence of intellectual capital and good corporate governance (namely: number of board directors, number of independent directors, audit committee meetings size) on financial performance in Asian telecommunication industries. This study employing 8 Asian companies from telecommunication sector listed in New York Stock Exchange (NYSE) with a total of 48 surveillance during the 2016-2021 sample years.